Etude des propriétés du biochar Application dans le traitement des eaux - ياسين, حاوي; نور الدين, صحراوي (University of El-Oued, 2020)
"This study is in the field of water treatment and its main objective is the elimination of diclofenac by adsorption on pomegranate skin biochar subjected to pyrolysis at 700°C (PG700). This study first covers general information on pharmaceutical substances, focusing on diclofenac and general information on adsorption and carbon. Secondly, the experimental protocol and the performance of the preparation tests, properties of biochar (PG700) and adsorption of DCF on biochar (PG700) in distilled water, by studying the effect of the various reaction parameters on the mechanisms of adsorption, the results obtained showed that: The adsorption capacity of PG700 vis-à-vis DCF ions is very high and it depends on several reaction parameters. The elimination of DCF by using biochar PG700 is slow (2 hours) with an elimination yield of 56.55% for an initial DCF content of 200 mg / l. The best results from adsorption of DCF to PG700 were obtained in an acidic medium (pH 3, 4, 5). The best isotherm that represents the experimental data of the adsorption of DCF by PG700 is the Langmuir model." "هذه المذكرة في مجال معالجة المياه وهدفها الرئيسي إزالة الديكلوفيناك عن طريق الامتزاز بواسطة الفحم النباتي لقشور الرمان (PG700) المتعرض للانحلال الحراري عند درجة مئوية ° 077 ، تحتوي هذه الدراسة أولا ا على معلومات عامة عن المواد الصيدلانية مع التركيز على الديكلوفيناك، عن عملية الامتزاز وعن الفحم، ثانياا البروتوكول التجريبي وأداء الاختبارات لتحضير وتوصيف الفحم النباتي (PG700) وامتصاص DCF على الفحم النباتي (PG700) في الماء المقطر، من خلال دراسة تأثير معاملات التفاعل المختلفة على آليات الامتزاز، أظهرت النتائج التي تم الحصول عليها أن : قدرة الامتصاص ل PG700 مقابل أيونات DCF تعتبر مهمة ج ا دا وتعتمد على العديد من معاملات التفاعل، إزالة DCF باستخدام PG700 بطي ئاة )ساعتان( مع كفاءة إزالة بلغت 56.55 ٪ لتركيز 077 مغ/ل من DCF . كما تم الحصول على أفضل النتائج لامتصاص DCF بواسطة PG700 في وسط حمضي ) pH )5 ،4 ،3 = وأفضل نموذج يمثل البيانات التجريبية لامتصاص DCF بواسطة PG700 هو نموذج Langmui"
Conception et diagnostic du système d'AEP et d'Assainissement- مذكرة ماستر تخصص
Keywords: Adsorption, Diclofenac (DCF), biochar (PG700), kinetics, isotherm.; الامتزاز، ديكلوفيناك ) DCF (، الفحم النباتي ) PG700 (، الحركية، الأيسوثرم